PENGARUH KEPUASAN ATAS GAJI DAN KOMITMEN ORGANISASI TERHADAP TURNOVER INTENTION DI RS. PKU MUHAMMADIYAH BLORA - Koma Arianti; Triyanto Triyanto (STIE Atma Bhakti, 2020)
This study aims to determine the effect of salary satisfaction and organizational commitment on employee turnover intention. Data collection from 50 respondents who work at the Blora Muhammadiyah Ummat Welfare Development Hospital was carried out using a questionnaire instrument. For the data analysis process using SPSS Version 21 software. The results of the study concluded that satisfaction with salaries and organizational commitment had a significant effect on employee turnover intention.